L’exemple du musée Nicéphore Niépce (Chalon-sur-Saône) : conservation, documentation et valorisation des photographies de presse - Sylvain Besson (In Situ)
In spite of its name, the Nicéphore Niépce museum at Chalon-sur-Saône is not exclusively devoted to the invention of photography. The whole history of photography is dealt with by the museum, from Niépce to the most recent advances in the realm of digital photography, from art photography to amateur photography and from industrial production to photo-reportage. Since its creation in 1972, the museum has built up a rich collection of more than three million photos, 6,000 cameras, 25,000 photography books and 40,000 magazines of, or about, photography. Press photos represent one of the main sectors in which the collections are growing richer and in which the museum is undertaking studies and organising exhibitions. Some collections of press photo prints were already included in the museum’s reserves (Chusseau-Flaviens, Rol agency) but over the last twenty years the museum has become more systematic in its prospection for photo magazines (complete collections whenever possible) and the archives of photographers working for the press (complete collections where possible, including negatives, contact sheets, layout prints, publication documents, notebooks, etc.) After their cataloguing, analysis, documentation and digitisation, the museum promotes these collections by organising exhibitions. These are not merely moments of delectation amongst pictures that are already familiar, but complex experiences of immersion, exploration and discovery of a particular photographer’s ways of seeing. The museum has also developed multimedia displays which are integrated into the exhibitions or made available online, explaining the history of a magazine, the context of its publication, the specificities of its design and its appreciation by the public of its time.